The Effect of Auditory Visual Learning Styles Supported By Interactive Youtube Videos on Learning Activities in Islamic Religious Education and Character Education Students - Okky Damayanti; Ruswanto Ruswanto; Ais Isti’Ana (Hikmah, 2025)
This study was motivated by the problem of low student learning activity in Islamic Religious Education and Ethics classes, especially verbal and mental activities, which are still dominated by conventional methods and the use of less varied learning media. This condition calls for learning strategies that accommodate differences in student learning styles in the digital age. This study aims to determine the effect of auditory and visual learning styles assisted by interactive YouTube videos on student learning activity at SMA Negeri 3 Bandar Lampung. The study uses a quantitative approach with a comparative causal (ex post facto) design. The sample consisted of 70 students selected through simple random sampling. Data were collected using a Likert scale questionnaire to measure learning styles and learning activity, then analyzed using regression tests. The results showed that auditory and visual learning styles supported by interactive YouTube videos had a significant effect on student learning activity. The novelty of this research lies in the integration of two learning styles with YouTube media in the context of Islamic religious education. The implications emphasize the importance of utilizing interactive, learning-style-based media to design more effective, participatory, and relevant Islamic religious education learning strategies.